2012
DOI: 10.3176/eco.2012.2.02
|View full text |Cite
|
Sign up to set email alerts
|

Defining the coastal water quality in Estonia based on benthic invertebrate communities

Abstract: The European Union Water Framework Directive requires that all member states assess the status of their coastal areas and develop or use existing classification systems to support future monitoring. To set the quality assessment system for the Estonian coastal sea, the composition of modern zoobenthic communities was compared to the communities from the 1950s-1960s. Sensitivity values of benthic taxa were determined, and the macrozoobenthic community index ZKI and boundaries for the classification system were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Although for the part of the considered species (e.g. Oligochaeta, Chironomidae, Bithinia, Erpobdella, Glossiphonia, Sphaerium) sensitivity scores were consistent with the results reported by other studies in the region (Osowiecki et al 2008, Kotta et al 2012, HELCOM 2013, others could be artificially elevated or vice versa demoted due to their preference for modified habitats or other particular inter-specific relationships with zebra mussel. Referring to the results presented, the simplest solution is to eliminate samples with zebra mussel (or any other IAS with strong impact on habitats and communities) from the benthic quality assessment.…”
Section: Discussionsupporting
confidence: 80%
“…Although for the part of the considered species (e.g. Oligochaeta, Chironomidae, Bithinia, Erpobdella, Glossiphonia, Sphaerium) sensitivity scores were consistent with the results reported by other studies in the region (Osowiecki et al 2008, Kotta et al 2012, HELCOM 2013, others could be artificially elevated or vice versa demoted due to their preference for modified habitats or other particular inter-specific relationships with zebra mussel. Referring to the results presented, the simplest solution is to eliminate samples with zebra mussel (or any other IAS with strong impact on habitats and communities) from the benthic quality assessment.…”
Section: Discussionsupporting
confidence: 80%
“…Unfortunately, due to the differences in methods, it is hard to compare how the species diversity has changed. Nevertheless, earlier studies demonstrate that the present-day communities are more uniform (shown by lower dissimilarities/distances between the stations) compared to the past communities (Kotta et al, 2012). Besides, the decline of phytophilous species in the northern part of the gulf was documented by Kotta & Kotta (1997).…”
Section: Discussionmentioning
confidence: 93%
“…Specifically, strong gradients were observed in water chlorophyll a along the major river mouths; moreover, such gradients matched with the biomass pattems of the suspension-feeding bivalves. This advocates the use of invertebrate biomass rather than abundance for the assessment of the status of the Gulf of Riga coastal areas in the frame of The European Union Water Framework Directive (Kotta et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to have positive effects on biodiversity on a larger scale, the action of designating protected areas should involve analyses of species distribution not just habitat-level mapping. Specifically, some areas need not host the habitat-forming species due to natural succession or anthropogenic disturbances (Kendrick et al, 2000;Kotta et al, 2012). Therefore, it is rewarding to perform a supplementary habitat suitability modelling in order to predict the potential of the environment for the species of high conservation value (Araújo & New, 2007) and use these modelled layers together with the actual mapping results when creating the boundaries of a protected area.…”
Section: Discussionmentioning
confidence: 99%